Tropical tropopause layer cirrus and its relation to tropopause. (February 2017) - Tseng, H.-H.; Fu, Q.
Abstract: This study examines the spatial and temporal patterns of tropical tropopause layer (TTL) cirrus clouds (i.e., clouds with bases higher than 14.5 km) and their relationship to tropical tropopause including both cold point tropopause (CPT) and lapse rate tropopause (LRT). We use eight years (2006–2014) data from the Cloud–Aerosol Lidar and Infrared Pathfinder Satellite Observations (CALIPSO) and Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) measurements. In addition to the CALIPSO cloud layer product, the clouds included in the current CALIPSO dataset as stratospheric features have been considered by separating clouds from aerosols, which are important in the TTL cloud analysis. It is also shown that the temporal variation of the stratospheric aerosols matches well with the volcanic eruption events. The TTL cloud fraction and the tropical tropopause temperature both have pronounced annual cycles and are strongly negatively correlated both temporally and spatially. The examination of the TTL cloud height relative to tropopause from collocated CALIPSO and COSMIC observations indicates that the tropopause plays a critical role in constraining the TTL cloud top height. We show that the probability density function of TTL cloud top height peaks just below the CPT while the occurrence of TTL clouds with cloud tops above the CPT could be largely explained by observed tropopause height uncertainty associated with the COSMIC vertical resolution. Highlights: The spatial and temporal patterns of tropical tropopause layer cirrus clouds and their relationship to tropical tropopause are examined by CALIPSO and COSMIC observations. To better quantify the TTL clouds, the clouds included in the current CALIPSO dataset as stratospheric features have been considered in addition to the CALIPSO cloud product, which is important for the TTL cloud analysis. The TTL cloud fraction and the tropical tropopause temperature both have pronounced annual cycles and are strongly negatively correlated in both space and time. The examination of the TTL cloud height relative to tropopause from collocated CALIPSO and COSMIC observations indicates that the tropopause plays a critical role in constraining the TTL cloud top height. The probability density function of TTL cloud top height peaks just below the CPT while the occurrence of TTL cloud with cloud tops above the CPT could be largely explained by observed tropopause height uncertainty associated with the COSMIC vertical resolution.